Bonnie Fournier 'Missing Women's Commission of Inquiry' Testimony 2 Part III - Fournier, Bonnie; Interviewer: Harrison, Don; Oral Testimony Archivist(s): Harrison, Don; Principle Investigator: ross, Dr. annie (Simon Fraser University, 2012)
Disclaimer: All testimonies are the experiences and beliefs of the individuals interviewed.